Scratch + CNC: Mixing Physical and Digital Worlds - Maraschin Jr, Dirceu; Gutierres, Anderson; Primo, Tiago Thompsen (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and EducationDO - 10.5753/wave.2020.212084, 2021)
Knowledge retention occurs most effectively when there is experimentation and there is an association between understanding what was learned conceptually and a real experience. We propose the development of an extension for Scratch 3.0 allowing the interaction with a CNC (Computer Numeric Control) machine. A proposal of cooperation between two environments in the learning context is created, combining programming in blocks with equipment able to provide outputs in physical objects.